The Role of Learning Arabic to Improve the Moderate Character - Auliyalloh, Binti Aghnia; Muttaqin, Mirza; Hariry, Ahmad Fawaid; Mustofa, Syaiful (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
This research aims to explore the role of Arabic language learning in improving the moderate character of students Ma'had Sunan Ampel Al-Aly, Maulana Malik Ibrahim State Islamic University, Malang. The research method uses a qualitative approach. Data is collected through interviews, observations and documents. The research object is students Ma'had Sunan Ampel Al-Aly, with a sample of thirty students. The results of the research show Arabic language learning at Ma'had Sunan Ampel Al-Aly Maulana Malik Ibrahim State Islamic University Malang significantly improves students' moderate character through ta'lim afkar, ta'lim al-Quran, and shabahul lughah activities which specifically contribute to strengthening moderate attitudes, in the form of values of tolerance, religious commitment, non-violence and friendliness to local culture. This finding is significant because it establishes the specific function that Arabic language learning programs have in developing moderate character. It also offers an empirical basis for educational strategies that effectively promote diversity values in the classroom.